Procedural Justice as a Moderator of Compensation, Ethical Awareness, and Work Discipline on Employee Integrity in Indonesian Immigration Institutions - Helmi Abdillah; Eka Yudhyani; Andi Indrawati; Nor Ratna Masrom (Politeknik Siber Cerdika Internasional, 2026)
Background: One of the key components of good governance is employee integrity, and Indonesian immigration institutions are no exception; corruption in the form of bribery, forgery of documents, and abuse of authority remains a high risk. Despite repeated reform attempts, integrity violations continue to erode public confidence in immigration services. Objective: This study examines the effect of procedural justice on the performance and ethical behavior of employees within Indonesian immigration institutions. Methods: We employed a quantitative research approach using SEM-PLS to test the introduced hypotheses. We used a structured questionnaire administered to 239 randomly selected officers from three immigration offices: Soekarno-Hatta, Batam, and Entikong. The model investigated both direct effects and moderating relationships between the analyzed variables. Results: The findings indicate that ethical awareness (EA) and work discipline (WD) are positively related to integrity, but compensation is not directly associated with integrity. Most significantly, procedural justice moderated the relationships between both compensation and ethical awareness and employee integrity indicating that perceiving organizational procedures as fair amplified the moral impact of both material rewards and moral awareness. However, procedural justice was not statistically significant as a moderator for the relationship between work discipline and employee integrity, meaning the effect of discipline does not strongly rely on perceived procedural fairness. Conclusion: Immigration institutions should strive for decision-making that reflects procedurally just ideals not only as a governance end, but also as a multiplier amplifying the effects of ethical awareness and fair compensation to foster sustained integrity-based practices among officers.